Self Help Group: An Effective Approach for Empowerment of Women - Lakhwinder Kaur , R. K. Kalra and R.K.Dhaliwal, (Indian Journal of Extension Education, 2014)
The present study focussed on the economic, social and managerial impacts of self help groups on empowering women.The study was conducted in three cultural zones of Punjab. A sample of 200 members of self help groups belonging tothese zones were the respondents of the study. An interview schedule was used to document the impact of self help groups.The findings of the study clearly revealed economic empowerment of rural women. The economic benefits gained fromenrolling in the groups were 'higher price of their products instead of selling individually' (91%) and 'understood bankingoperations to avail credit facility' (81.50%). A large number of women in Punjab developed 'courage to thinkindependently' (99.50%), 'understood group activities' (96%) and 'managed group activities' (95.50%) after joining thegroup. Furthermore the social empowerment of the members in terms of team spirit (97%), talking freely within family(94%), confidence in dealing with people (95.50%) were enhanced. It indicates that self help groups bring economicupliftment, leadership skills in managing the group and inculcate great confidence in the members of selected groups tosucceed in their day to day life.